Strategy, Control Systems, and Resource Sharing: Effects on Business-Unit Performance - Govindarajan, Vijay; Fisher, Joseph G. (Academy of Management Journal, 1990)
Focusing on business units (SBUs) in diversified firms, this study investigated the relationships among control systems, resource sharing, and competitive strategies and their interactive effects on SBU performance. Empirical results indicate that output control and high resource sharing are associated with higher effectiveness for a low-cost strategy and behavior control and high resource sharing are associated with higher effectiveness for a differentiation strategy.